Job satisfaction: An explorative study on work characteristics changes of employees in Intralogistics 4.0 - Sven Winkelhaus; Eric H. Grosse; Christoph H. Glock (Journal of Business Logistics, 2022)
The increasing trend toward digitalization in logistics poses a significant managerial challenge, particularly by fundamentally changing the traditional, manual workplaces in intralogistics. Although intralogistics processes have, in some cases, already been automated or are supported by smart technologies, humans remain an inevitable part of future intralogistics but with changing work characteristics. This study aims to examine the influences of the transition toward Intralogistics 4.0 on work characteristics of intralogistics employees. First, a systematic literature review on work characteristics and job satisfaction in a broader Logistics 4.0 context was conducted. Thereafter, a qualitative, explorative methodology was employed to examine the perception of work characteristics that impact job outcomes such as job satisfaction, motivation, and performance at different Intralogistics 4.0~maturity levels. The results of semi-structured interviews conducted across seven companies demonstrated the significant, heterogeneous changes of work characteristics related to the type of technology applied in Intralogistics 4.0. Our findings indicate that the development toward Intralogistics 4.0-implemented workplaces does not have a simple or predefined impact on humans; instead, the individual design is relevant and can improve the workplaces with more opportunities for satisfying and motivating jobs.
Keywords: 650; Industry 4.0; Intralogistics 4.0; Intralogistics 4.0~maturity; Job characteristics; Job satisfaction; Logistics 4.0; Qualitative interview; Systematic literature review